Investigating the space recognation and soundmarks in open semi-open and enclosed spaces via semantic ratings - Bora, Zeynep; Yilmazer, Semiha (AESOP, 2015)
The aim of the study is to increase the samples in enclosed soundscape studies and as a public space; metro stations have been aimed to be included into the literature. This study is a subjective approach; examines the relationship between soundmark a space and space recognation within “degree of enclosure” context in order to gain data, sound recordings were taken from site and a listening test applied to investigate if spaces could be recognized/understood just by hearing. For each sound recording, subjects were asked to explain the recorded space (if they are open/semi open/enclosed space), and define the sound sources. Besides, in order to understand sound quality of the selected spaces, subjects were asked to choose from 17 pairs adjectives for each recording, which were selected from the previous studies. Results showed that, all of the subjects determined open spaces correctly, enclosed spaces were determined with 84% while 95% of the subjects have failed to identify the semi open spaces. Only half of the subjects were able to determine the usage of the spaces. As soundmarks, bird, wind, and water sounds were defined in the open space, pay gates and coin sounds were defined in the semi-open space, and the metro itself, as well as its brakes, doors, and announcement system were defined in the enclosed space. For open spaces, subjects tended to choose adjectives as “pleasant”, “calming”, “natural”; while for enclosed spaces tended to choose “unpleasant”, “stressing”, “artificial”, etc.
Book of proceedings: Annual AESOP Congress, Definite Space – Fuzzy Responsibility, Prague, 13-16th July, 2015